On the taxonomy of the genus Tumicla Wallengren, 1863 with description of two new species from Mozambique (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V.; László, Gyula M. (Zootaxa, 2018)
The paper presents an overview of the Afrotropical genus Tumicla Wallengren, 1863 and the updated checklist of all currently known species of this genus belonging to the tribe Lithosiini. We propose 18 new combinations: Tumicla atricraspeda (Hampson, 1914), comb. nov., T. calimerae (Durante, 2008), comb. nov., T. congoensis (Kühne, 2007), comb. nov., T. dimidiata (Durante, 2008), comb. nov., T. distyi (Kühne, 2007), comb. nov., T. doa (Kühne, 2007), comb. nov., T. eala (Kühne, 2007), comb. nov., T. fasciata (Durante, 2008), comb. nov., T. gigantea (Kühne, 2007), comb. nov., T. hermanni (Kühne, 2007), comb. nov., T. mutabilis (Kühne, 2007), comb. nov., T. retromaculata (Durante, 2008), comb. nov., T. rosea (Durante, 2008), comb. nov., T. rubea (Durante, 2008), comb. nov., T. russula (Kiriakoff, 1963), comb. nov., T. similis (Durante, 2008), comb. nov., T. spinata (Kühne, 2007), comb. nov., and T. versicolor (Kühne, 2007), comb. nov. Two new species of Tumicla, T. tsonga sp. nov. and T. arktos sp. nov. are described from southern Mozambique.